Total Talar and Navicular Extrusions: A Case Report. Issue 2 (22nd April 2022) - Lalchandani, Gopal R.; Hung, Nicole J.; Janghala, Abhinav; Terry, Michael; Morshed, Saam
Abstract : Case: A 15-year-old adolescent boy sustained both talar and navicular extrusions after a dirt-bike accident. The talus and navicular were discarded during initial debridement because of contamination. Given extensive soft-tissue injury and bone loss, the patient's family opted for transtibial amputation, as described by Ertl, over limb salvage. Simultaneous osteomyoplastic reconstruction and acute targeted muscle reinnervation were performed. Conclusion: Transtibial amputation is a viable treatment option for total talar and navicular extrusions, particularly if an optimal functional outcome is unachievable with limb salvage. Simultaneous osteomyoplastic reconstruction and acute targeted muscle reinnervation can potentially decrease neuroma formation and phantom limb pain.